March and the pursuit of organizational intelligence: the interplay between procedural rationality and sensible foolishness. (28th November 2019) - Ocasio, William; Rhee, Luke; Boynton, Dylan
Abstract: March's long and varied career in organization theory encompasses a number of seemingly disparate themes from rationality, to ambiguity and the garbage can model, to exploration and exploitation in organizations. We examine March's diverse research trajectory and conclude that his different insights can be brought together under one common theme for his career: that both procedural rationality and sensible foolishness are necessary for the pursuit of organizational intelligence. Traditional models of rationality, even bounded rationality, are insufficient because goals are unstable and inconsistent, and causal ambiguity leads to myopic learning or worse. To explain the interplay between procedural rationality and sensible foolishness in organizations, we explore their role in the inter-related processes of programing, monitoring, sensemaking, search, and decision making.